The Implementation of Constructivism Learning in Islamic Religious Subject At Senior High School Plus Bina Insani - Oktavita Sari (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
Constructivism approach in teaching and learning is based on a synthesis of several research in cognitive psychology and social psychology, as well as techniques of operant conditioning theory in behavioral psychology. The basic premise is that individuals must actively